MATERIAL ENTANGLEMENTS OF COMMUNITY SURVEILLANCE & INFRASTRUCTURAL POWER - Bridges, Lauren E. (AoIR Selected Papers of Internet Research, 2020)
Through the case study of Amazon Ring's cameras, this paper explores the deepening material and discursive alliance between public and private institutions in the building of digital infrastructures that support the development of community surveillance. The analysis reveals a complex supply-chain network entangled with histories of settler-colonialism, racialization and gendered inequities. Bolstered by developments in cloud computing, concealing the human and nonhuman supply-chains, these systems are never detached from material inputs; rather, they are embedded in vast infrastructural systems and complex transnational supply chains powered by logics of extraction, circulation and accumulation of capital. I argue that Amazon Ring cameras are an articulation of “infrastructural power” defined by Laleh Khalili (2018: 915) as an assemblage of “practices, discourses, physical fixtures, laws and procedures” with the aim of (re)producing capitalist relations. Through a material and discursive analysis, this paper aims to draw into the light the complex human and non-human entanglements that constitute community surveillance networks in order to move towards an infrastructural critique so that we may more effectively evaluate the social costs of digital systems that can never be detached from their material and human creators.